Ouabain, a cardiac glycoside, inhibits the Fanconi anemia/BRCA pathway activated by DNA interstrand cross-linking agents. - Dong Wha Jun; Mihwa Hwang; Hyun Jung Kim; Soo Kyung Hwang; Sunshin Kim; Chang-Hun Lee (PLoS ONE, 2013)
Modulation of the DNA repair pathway is an emerging target for the development of anticancer drugs. DNA interstrand cross-links (ICLs), one of the most severe forms of DNA damage caused by anticancer drugs such as cisplatin and mitomycin C (MMC), activates the Fanconi anemia (FA)/BRCA DNA repair pathway. Inhibition of the FA/BRCA pathway can enhance the cytotoxic effects of ICL-inducing anticancer drugs and can reduce anticancer drug resistance. To find FA/BRCA pathway inhibitory small molecules, we established a cell-based high-content screening method for quantitating the activation of the FA/BRCA pathway by measuring FANCD2 foci on DNA lesions and then applied our method to chemical screening. Using commercial LOPAC1280 chemical library screening, ouabain was identified as a competent FA/BRCA pathway inhibitory compound. Ouabain, a member of the cardiac glycoside family, binds to and inhibits Na(+)/K(+)-ATPase and has been used to treat heart disease for many years. We observed that ouabain, as well as other cardiac glycoside family members--digitoxin and digoxin--down-regulated FANCD2 and FANCI mRNA levels, reduced monoubiquitination of FANCD2, inhibited FANCD2 foci formation on DNA lesions, and abrogated cell cycle arrest induced by MMC treatment. These inhibitory activities of ouabain required p38 MAPK and were independent of cellular Ca(2+) ion increase or the drug uptake-inhibition effect of ouabain. Furthermore, we found that ouabain potentiated the cytotoxic effects of MMC in tumor cells. Taken together, we identified an additional effect of ouabain as a FA/BRCA pathway-inhibiting chemosensitization compound. The results of this study suggest that ouabain may serve as a chemosensitizer to ICL-inducing anticancer drugs.